Creating and Using Fiscal Space for Accelerated Development in Liberia - Lofgren, Hans (World Bank, Washington, DC, 2014)
This paper presents simulations for the period 2013-2030 of measures that permit increased spending on infrastructure and human development, the priority areas in Liberia's 2013-2017 "Agenda for Transformation" and for its national vision, Liberia Rising 2030. The simulations are carried out with a Liberian version of MAMS (Maquette for Millennium Development Goals Simulations), a Computable General Equilibrium model. According to the results, among the key sources of fiscal space, foreign grants generate the best outcomes followed by improved government allocative efficiency. Taxes tend to involve trade-offs since they reduce resources for private consumption and investment, both of which tend to contribute to stronger macro and Millennium Development Goals performance. Increased foreign borrowing is less attractive since, in order to make a substantial difference, it would quickly add to the foreign debt, making the economy more crisis-prone and less flexible. The preferred balance between different uses of fiscal space depends on payoffs from different government functions, typically unknown or only appearing with a lag. Under the parameters used in the simulations, determined in light of fragmentary evidence, the outcomes were marginally stronger under a balanced approach with scaling up of both infrastructure and human development services. Balanced expansion may also contribute to efficiency and be easier for political reasons. A final finding is that it is possible to consider fiscal space issues in isolation from the mining sector: simulations suggest that the marginal effects of creating additional fiscal space are very similar irrespective of the level of mining export prices.